Central Iliac Arteriovenous Anastomosis for Uncontrolled Hypertension: One-Year Results From the ROX CONTROL HTN Trial. Issue 6 (December 2017) - Lobo, Melvin D.; Ott, Christian; Sobotka, Paul A.; Saxena, Manish; Stanton, Alice; Cockcroft, John R.; Sulke, Neil; Dolan, Eamon; van der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; et al.
Abstract : Creation of a central iliac arteriovenous anastomosis using a novel nitinol coupler device results in an immediate, significant reduction of blood pressure (BP). We present efficacy and safety findings at 12 months post-coupler insertion. This open-label, multicenter, prospective, randomized trial enrolled patients with a baseline office systolic BP ≥140 mm Hg and average daytime ambulatory BP ≥135/85 mm Hg. Subjects were randomly allocated to coupler implantation and continuing previous pharmacotherapy or to maintain previous treatment alone. At 12 months, 39 patients who had coupler therapy were included in the intention-to-treat analysis. Office-based systolic BP reduced by 25.1±23.3 mm Hg (baseline, 174±18 mm Hg; P <0.0001) post-coupler placement, and office diastolic BP reduced by 20.8±13.3 mm Hg (baseline, 100±13 mm Hg; P <0.0001). Mean 24-hour ambulatory BP reduced by 12.6±17.4/15.3±9.7 mm Hg ( P <0.0001 for both). In a prespecified subset of patients who failed to respond adequately to prior renal denervation, coupler therapy led to highly significant reduction in office systolic/diastolic BP (30.7/24.1 mm Hg) and significant reduction in 24-hour ambulatory systolic/diastolic BP (12.4/14.4 mm Hg) at 12 months (n=9). After coupler therapy, 14 patients (33%) developed ipsilateral venous stenosis; all were treated successfully with venous stenting. These findings confirm the importance of arterial mechanics in the pathophysiology of hypertension and support the clinical use of a central iliac arteriovenous anastomosis. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01642498. Abstract : Supplemental Digital Content is available in the text.